Impact of trade liberalisation on formal-informal interlinkages in India: Does sectoral labour mobility matter? - Anirban Kundu (Journal of Economic Structures, 2020)
Existing study argues that labour market flexibility accompanied by trade liberalisation helped in building complementary relationship between formal and informal sectors in India. However, no direct relation is established between the labour market flexibility and trade liberalisation with respect to inter- and intra-sectoral movement of labour. The present study enquires whether the extent of labour mobility between and within formal-informal sectors affects the formal-informal growth linkages due to the tariff cut on traded goods, as a part of trade liberalisation in India. The findings based on static CGE analysis indicate that in absence of labour market segmentation (i.e. in absence of both wage rigidity and skill specificity) with full mobility of labour, formal sector growth is higher vis-à-vis the growth of those activities under segmented labour market with full mobility of labour. Amongst growing informal sector activities, output growth is lower in absence of segmented labour market with full mobility of labour. Finally, restricted labour mobility leads to largest expansion of formal activities, but further exacerbates the growth of informal activities. The study reveals that improvement in functional income distribution is mixed across households, depending on the degree of labour mobility, which implies labour market adjustment is costly due to structural reforms, that pitches for government intervention.
Keywords: O17; F62; F66; J62; C63; 330; Formal-informal interlinkages; Trade liberalisation; Segmented labour market; Labour mobility; Static CGE model